Magnetic Resonance Imaging Validates the Clinical Accuracy of the Mcmurray's Test in Diagnosing Medial Meniscal Tears - Ziyad Ahmad, Muhammad Imran Farid, Muhammad Taha Khalil, Fazli Wajid, Amanullah Khan, Syed Abdur Rub Abidi, Zain Nayyer, Nada Ullah, Muhammad Inam, (Pakistan Journal of Medical & Health Sciences, 2024)
Background: A physical examination method to find medial meniscal tears is the McMurray's test. The purpose of this research was to evaluate how effectively the McMurray's test can identify medial meniscal tears in a clinical situation that have been verified by MRI. However, arthroscopic evaluation is now replacing the traditional methods. Aim: To determine diagnostic accuracy of McMurray's test is in diagnosing Medial Meniscal knee injuries. Methods: This prospective case series study was conducted in the department of Orthopedic MTI Lady Reading Hospital Peshawar on 100 consecutive patients who received an MRI for suspected medial meniscal tears between August 2022 and July 2023. Each patient underwent the McMurray's test, and the findings were compared to those of the MRI scans. Positive and negative predictive values, as well as the sensitivity and specificity of the McMurray test, were calculated. The McMurray test was performed on all patients to check for meniscal tears, and arthroscopy was then performed on the affected knees to evaluate the accuracy of the test. Results: Overall, one hundred patients took part in the study. There were 65 males and 35 females among the patients. There was a wide range of ages represented in the group, from 18 to 75. A total of 45 out of the 100 cases were young adults. The mean age was 31.46, while the standard deviation was 9.12 years. Participants of all ages were involved in the study. Forty-seven patients (47%) were in the 18-30 age range, 25(25%) were in the 31-45 age range, 19(19%) were in the 46-60 age range, and 9(9%) were in the 61-75 age range. In 100 patients MRI and McMurray tests can diagnose medial meniscal abnormalities. According to the study, the sensitivity of McMurray's test is 62.9%, the specificity is 81.6%, the positive predictive value is 84.8%, and the negative predictive value is 57.4%. Practical Implication: McMurray's Test is a good alternative to MRI for diagnosis of medial meniscus in areas where the facility of imaging is not available. Conclusion: The McMurray's test is a good clinical method for detecting medial meniscal tears that has been verified by magnetic resonance imaging (MRI). Keywords: McMurray test, meniscal tears, Magnetic Resonance Imaging, arthroscopy, accuracy.